Urban Renewal Strategies and Economic Growth in Ondo State, Nigeria: A Case Study - Joseph Adeniran Adedeji; Olatunde Arayela (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
One of the negative effects of the high rate and pace of urbanisation in developing countries is the decay of urban centres. While this decay has eaten deep into the fabric of these settlements turning them into urban slums and ghettoes with poor infrastructure, the effects of the decay are multifarious. Despite the fact that the economy is the “life-wire” of urban centres, its untold downturn consequent upon urban decay is unimaginable because of the relationship that exists between environmental quality and economic growth. This calls for a proactive approach called urban renewal towards the creation of successful urban places. This paper, therefore, reviews urban renewal strategies and their implications on economic growth with a particular focus on Ondo State, Nigeria towards identifying the means of enhancing the sustainability of its economic proceeds. The study relied on secondary information sources and discovered that appropriate urban renewal strategies yields corresponding economic growth. The paper asserts that the urban renewal fit achieved in the state during the period 2009 to 2012 can be replicated in other states in Nigeria if similar political willpower is available. The paper recommends the participation of the public combined with appropriate strategies in urban renewal schemes for the best result and argues in conclusion that urban renewal is the only feasible solution to the current dwindling economic sector in Nigeria and other developing economies.